A política de acolhimento de refugiados – considerações sobre o caso Português - Costa, Bruno Ferreira (2018)
The outbreak of armed and civil strife in the Middle East, as well as the expansion of the self-proclaimed Islamic State, has led to a considerable influx of refugees into the European Community space, the largest wave since the Second World War. The attractiveness of the European area, coupled with host policies, is the starting point for this analysis, which focuses on the reception mechanisms registered by the Portuguese State. Through an imminently exploratory study and using the descriptive analysis method, we opted to analyze the reception strategies as well as the existing data on the processes in force in Portugal, also considering a comparative view with the other Member States of the European Union.